2019
DOI: 10.1101/716001
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Autonomous emergence of connectivity assemblies via spike triplet interactions

Abstract: AbstractNon-random connectivity can emerge without structured external input driven by activity-dependent mechanisms of synaptic plasticity based on precise spiking patterns. Here we analyze the emergence of global structures in recurrent networks based on a triplet model of spike timing dependent plasticity (STDP) which depends on the interactions of three precisely-timed spikes and can describe plasticity experiments with varying spike frequency better than the classical pair… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 122 publications
1
21
0
Order By: Relevance
“…The triplet STDP rule describes synaptic plasticity based on triplets of spikes and captures experiments where the rate of pre- and postsynaptic neurons varies ( 58 ). The triplet STDP rule enables the formation of bidirectional connections, a necessity for the formation of clustered architectures ( 41 , 59 ). According to this rule, the synaptic strength from excitatory neuron to excitatory neuron follows: Here, and are the amplitude of the weight change induced by a post–pre pair or a post–pre–post triplet of spikes.…”
Section: Methodsmentioning
confidence: 99%
“…The triplet STDP rule describes synaptic plasticity based on triplets of spikes and captures experiments where the rate of pre- and postsynaptic neurons varies ( 58 ). The triplet STDP rule enables the formation of bidirectional connections, a necessity for the formation of clustered architectures ( 41 , 59 ). According to this rule, the synaptic strength from excitatory neuron to excitatory neuron follows: Here, and are the amplitude of the weight change induced by a post–pre pair or a post–pre–post triplet of spikes.…”
Section: Methodsmentioning
confidence: 99%
“…Since the memories are in our model stored in the synapses between excitatory neurons, only these are plastic. Previous theoretical work has shown that learning [15,20] or spontaneous emergence [16,19] of static assemblies as well as their maintenance can be enabled by a combination of STDP and homeostatic plasticity. A recent study investigated STDP in the recurrent excitatory synapses of the hippocampal region CA3 [26], i.e.…”
Section: Models and Approachesmentioning
confidence: 99%
“…For faithful memory storage the ensemble of neurons forming an assembly is assumed to remain the same [12]. Previous theoretical analysis has carefully studied the formation and maintenance of such static neuronal assemblies [13,14,15,16,17,18,19]. In particular, it has been suggested that in presence of noisy, irregular spiking activity [14,20,15,16] and spontaneous synaptic changes [18] assemblies are preserved with the help of activity dependent synaptic plasticity.…”
mentioning
confidence: 99%
“…In particular, Ravid Tannenbaum et al showed that in networks of Poisson neurons synfire chains and self connected assemblies can emerge autonomously in recurrent networks [ 46 ]. Montangie et al showed that a more realistic form of STDP based on spike triplets also leads to autonomous emergence of assemblies [ 47 ].…”
Section: Introductionmentioning
confidence: 99%